2015
DOI: 10.1007/s10008-015-2962-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high-voltage spinel LiNi0.5Mn1.5O4 material for lithium-ion batteries by a metal-cholate supramolecular hydrogel as precursor

Abstract: High-voltage cathode material LiNi 0.5 Mn 1.5 O 4 has been first synthesized by a novel metal-cholated supramolecular hydrogel as precursor. The structural analysis was investigated by X-ray powder diffraction, scanning electronic microscope, and Fourier transform infrared spectroscopy. The results indicated that the as-products possessed well constructed spinel structure and high crystallinity and pure phase through adding optimal amount of cholic acid. The electrochemical properties were also investigated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…[78] Recently, it has been demonstrated that metal cholate hydrogels facilitated the fabrication of complex metal oxides with controlled stoichiometry. [79] Li-Ni-Mn cholate hydrogel was prepared and converted to submicron powders of LiNi 0.5 Mn 1.5 O 4 spinel material for energy storage in lithiumion batteries. [79] The obtained cathode material showed enhanced electrochemical charge-storage properties.…”
Section: Fabrication Of Composite Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[78] Recently, it has been demonstrated that metal cholate hydrogels facilitated the fabrication of complex metal oxides with controlled stoichiometry. [79] Li-Ni-Mn cholate hydrogel was prepared and converted to submicron powders of LiNi 0.5 Mn 1.5 O 4 spinel material for energy storage in lithiumion batteries. [79] The obtained cathode material showed enhanced electrochemical charge-storage properties.…”
Section: Fabrication Of Composite Gelsmentioning
confidence: 99%
“…[79] Li-Ni-Mn cholate hydrogel was prepared and converted to submicron powders of LiNi 0.5 Mn 1.5 O 4 spinel material for energy storage in lithiumion batteries. [79] The obtained cathode material showed enhanced electrochemical charge-storage properties. [79] From the available literature, it becomes obvious that the gelforming properties of BAs/BSs provide a platform for many promising applications, such as the synthesis of NPs of controlled stoichiometry, size, and shape in a gel matrix.…”
Section: Fabrication Of Composite Gelsmentioning
confidence: 99%
“…In this method, the purity of the material depends on the starting materials, calcination temperature, and time. It is mentioned that the resultant products from these methods generally contain impurity phases such as NiO [26, 27] and Li x Ni 1− x O [28, 29] due to the oxygen loss at high temperature, which could lead to electrochemical deterioration and capacity fading.…”
Section: Synthesis Structure and Cycling Degradation Mechanism Of Lnmomentioning
confidence: 99%
“…It is believed that the mechanism of gelation is related to metal‐carboxyl cholate coordination, hydrogen bonding between cholate molecules and a delicate hydrophilic‐hydrophobic balance . The employment of trivalent lanthanides as metal cations has allowed the development of emissive soft materials with tunable luminescence . Other applications for divalent‐cholate hydrogels have been reported such as their use as precursors for the development of lithium‐based batteries …”
Section: Introductionmentioning
confidence: 99%
“…The employment of trivalent lanthanides as metal cations has allowed the development of emissive soft materials with tunable luminescence . Other applications for divalent‐cholate hydrogels have been reported such as their use as precursors for the development of lithium‐based batteries …”
Section: Introductionmentioning
confidence: 99%